2022
DOI: 10.2138/rmg.2022.88.09
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Inclusions in Fibrous Diamonds

Abstract: Giardini (1974, 1975) reported the composition of gases released by crushing diamonds under vacuum. Gas signals of transparent or light-yellow diamonds were similar to the system blank levels (0.2-2 × 10 −5 cm 3 STP, for an empty crushing chamber at 0 °C and 1 bar). However, the crushing of cubic and translucent diamonds at 200 °C yielded gas volumes that were an order of magnitude larger. The main gases released were H 2 O and CO 2 . Gas released by graphitization of diamonds contained mostly CO with minor H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 282 publications
(630 reference statements)
1
9
0
Order By: Relevance
“…These authors consider that during percolation of such saline high-pressure fluids, Cr could dissolve from the peridotitic wall rocks without significantly affecting their high Cr concentrations. The ability of such saline fluids to impose their high-Cr characteristics on garnet inclusions in diamond, however, is likely limited, given that their mean Cr# (100Cr/(Cr+Al)) is only 7.5 (high-density fluid compilation of Weiss et al 2022) compared to Cr# of 38-65 for the unusually Cr 2 O 3 -rich (> 13 wt%) garnet inclusions discussed here. In contrast, enrichment of Al in cratonic peridotites is frequently observed and possibly relates to fluids derived from recycled sediments (e.g., Rapp et al 2017).…”
Section: Key Observations and Conclusionmentioning
confidence: 94%
See 4 more Smart Citations
“…These authors consider that during percolation of such saline high-pressure fluids, Cr could dissolve from the peridotitic wall rocks without significantly affecting their high Cr concentrations. The ability of such saline fluids to impose their high-Cr characteristics on garnet inclusions in diamond, however, is likely limited, given that their mean Cr# (100Cr/(Cr+Al)) is only 7.5 (high-density fluid compilation of Weiss et al 2022) compared to Cr# of 38-65 for the unusually Cr 2 O 3 -rich (> 13 wt%) garnet inclusions discussed here. In contrast, enrichment of Al in cratonic peridotites is frequently observed and possibly relates to fluids derived from recycled sediments (e.g., Rapp et al 2017).…”
Section: Key Observations and Conclusionmentioning
confidence: 94%
“…This is because the four, six or twelve sided cavities of 1 to 5 µm size contained no solid material when broken or polished through. Subsequent studies have shown this not to be the case (Weiss et al 2022). Clouds range in color from white to mid-grey with an overall shape that can be irregular but is more often distinctly cuboid or star-shaped and visually aligned with the shape of the diamond.…”
Section: A History Of Inclusion Discovery In Lithospheric Diamondsmentioning
confidence: 99%
See 3 more Smart Citations